Implementation Of Individual Guidance Patterns In Learning To Recite The Quran For Students Of TPQ Manzilussakinah Candiroto, Candimulyo, Kertek, Wonosobo - Atika Lestari, Sindi; Aziz, Noor; Astina, Chairani (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
Learning to recite the Qur’an in the Qur'anic Education Park (TPQ) is important in the formation of the Qur'anic generation. However, differences in the ability of students and limited resources are often a challenge. One of the solutions applied at TPQ Manzilussakinah Candiroto, Candimulyo, Kertek, Wonosobo is the application of individual guidance patterns. The purpose of this study is to describe the implementation, obstacles, and supporting factors of the application of individual guidance patterns in learning to recite the Qur’an. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results showed that individual guidance allows teachers to provide personalized attention according to the ability of students, so that students more quickly understand makhraj, tajweed, and become more confident in reciting the Qur’an. It is known that this method strengthens the emotional involvement of teachers and students and creates a more conducive learning atmosphere. Although there are obstacles such as lack of parental involvement, the influence of gadgets, and time constraints, success is still achieved thanks to the support of competent teachers, the enthusiasm of students, and adequate learning facilities. In conclusion, the individual guidance pattern is proven to be effective and worthy of wider application in Qur'anic education.